2023
DOI: 10.1002/dmrr.3604
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Ramadan fasting: A randomised controlled trial for people with type 2 diabetes during Ramadan applying the principles of the ADA/EASD consensus

Abstract: Background Fasting during the holy month of Ramadan is one of the five pillars of Islam. Fasting is not meant to create excessive hardship on the Muslim individual according to religious tenets. It is important that health professionals are aware of potential risks associated with fasting during the month of Ramadan (mainly hypoglycemia and hyperglycemia). Aims To explore the impact of applying the principles of our 2020 recommendations for the management of type 2 diabetes (T2D) during the month of Ramadan. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Indeed, the majority of Muslims with diabetes continue to fast despite medical advice to the contrary [11,12] . However, there are signi cant hazards that fasting may entail [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the majority of Muslims with diabetes continue to fast despite medical advice to the contrary [11,12] . However, there are signi cant hazards that fasting may entail [13] .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study analyzed the impact of applying recommendations from the American Diabetes Association and the European Association for the Study of Diabetes (ADA/EASD) on management of T2D during Ramadan. 19 A multinational, randomized controlled trial (RCT) was conducted in five Muslim-majority countries. Six hundred and sixty participants were approached.…”
Section: Highlights Of the Literaturementioning
confidence: 99%
“…As a result, it has been observed that people observing a period of pre-Ramadan assessment with clinicians, as a personalized approach, could improve metabolic balance and also prevent acute complications during and after Ramadan period. 99,100 Nutrigenetics studies the role of genetic variants in the modulation of response to diet and the implications in the development, or prevention, of diseases. In particular, some genetic variants seem associated with diet response for what concerns the development of cardiovascular diseases, mainly obesity and diabetes.…”
Section: Dietmentioning
confidence: 99%